An optimal assignment with discrete target variable of processing time in reset limited-cycle multiple production periods. (13th January 2021) - Zhao, Xiaowen; Yamamoto, Hisashi; Sun, Jing
The real processing time of the worker follows a variety of probability distributions. The target processing time of each process is set. It is assumed that the real processing time may be shorter or longer than the target processing time. We consider the optimal assignment problem, where the arrangement of each worker will be obtained with the minimised total processing cost of the production line when the target processing work time follows the discrete distribution. In this paper, we deal with the optimal assignment rules with three kinds of workers under this LCMwMP (limited-cycle model with multiple periods) model. Additionally, some rules of workers' assignment optimisation are researched by numerical analyses.